Ethnolinguistics of Maluku Coastal Communities: Marine Biota Lexicon and Ecological Knowledge - Chrissanty Hiariej; Kedswin Gerson Hehanussa (Universitas Pattimura, 2026)
The Maluku Sea possesses exceptionally rich marine biodiversity and serves as the primary source of livelihood for coastal communities. This richness is reflected not only in economic aspects but also in the local knowledge system that has been passed down through generations through language, particularly in the lexicon of fish and marine biota. This study aims to describe the forms of fish and marine biota lexicons used by the people of Maluku and to reveal the ecological knowledge embedded within them. The study employs a qualitative descriptive approach from an ethnolinguistic perspective. Data in the form of local terms for fish and marine biota were collected through documentation, interviews, and observations of fishing communities in the coastal areas of Maluku. The findings indicate that the naming of fish and marine biota is not arbitrary; rather, it represents the community’s observations regarding color, body shape, behavior, habitat, seasonal occurrence, and the economic value of certain species. In addition, variations in fish names were identified across different coastal regions, reflecting the linguistic and cultural diversity of Maluku communities. These lexicons function not only as tools of communication but also as repositories of traditional ecological knowledge that are essential for the sustainable management of marine resources. Therefore, the documentation of fish and marine biota lexicons constitutes a strategic effort toward preserving the language, culture, and local knowledge of the coastal communities of Maluku.